Alterations in platelets during SARS-CoV-2 infection. (17th February 2022) - Brambilla, Marta; Canzano, Paola; Becchetti, Alessia; Tremoli, Elena; Camera, Marina
Abstract: Coronavirus disease 2019 (COVID-19) is a pandemic syndrome caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. SARS-CoV-2 infection induces a process of inflammation and thrombosis supported by an altered platelet activation state. This platelet activation is peculiar being characterized by the formation of platelet-leukocytes rather than platelet–platelet aggregates and by an increased procoagulant potential supported by elevated levels of TF positive platelets and microvesicles. Therapeutic strategies targeting, beyond systemic inflammation (i.e. with tocilizumab, an anti interleukin-6 receptor), this state of platelet activation might therefore be beneficial. Among the antithrombotic drugs proposed as candidates to treat patients with SARS-CoV-2 infection, antiplatelet drugs, such as aspirin are showing promising results.